Can Combination of Peripheral Nerve Block and Non-opioidal Patient Controlled Analgesia Be an Effective Postoperative Pain Control Method?. Issue 4 (16th October 2019) - Kang, Chan; Lee, Gi Soo; Kim, Dong Yeol; Lee, Jeong-kil; Ahn, Ki Jun; Hwang, Sung Jin; Seo, Gang Won; Kim, Yong Hwan; Lee, Sang Bum; Song, Jae Hwang
Category: Ankle, Pain medicine Introduction/Purpose: Even though bone surgery is very painful after operation, there is no established method to control postoperative pain due to efficacy and side effects. Ultrasound-guided peripheral nerve block (PNB) and nonsteroidal anti- inflammatory drugs (NSAIDs) patient controlled analgesia (PCA) can effectively control pain and reduce side effects. Methods: We conducted a prospective study of 150 patients over 18 years of age who underwent bone surgery from June 2018 to December 2018. All operations were performed under anesthetic ultrasound-guided PNB and additional PNB was performed to control postoperative pain. Among the 120 patients who participated in the final study, NSAIDs PCA was used in group A (65 patients) and NSAIDs PCA was not used in group B (55 patients) for pain control. Postoperative management except PCA was same in both groups. Pain scores are measured at 6, 12, 18, 24, 36, 48, and 72 hours after the operation and they were compared using visual analogue scale (VAS) pain scores. Survey was done on satisfaction of patients, and their willingness to reconsider same method of pain control when they undergo same surgery next time. Also, we evaluated possible side effects that might happen during process of controlling pain. Results: VAS pain score were significantly different only at 24 h postoperatively (p=0.004). In Group A, three patients were prescribed 3 amples of pethidine intramuscular injection as rescue analgesic. In group B, 35 patients were prescribed 50 amples of pethidine and 12 patients of them were received additional 18 amples of ketorolac intramuscular injection as rescue analgesic(p=0.000). In group A, all patients were satisfied with the pain control method, but 5 of the group B patients were dissatisfied (p=0.001). 3 patients responded to severe pain after operation and 2 of them due to postoperative nausea and vomiting (PONV). In group A, there were no patients complaining of PONV, but in group B, 5 patients complained of symptoms (p=0.018), and 3 of them were prescribed additional antiemetics (p=0.093). Conclusion: Combined use of ultrasound-guided PNB and NSAIDs PCA seems to be an effective postoperative pain control method in foot and ankle surgery. Because, pain can be effectively controlled and PONV can be reduced.